Do you know otitis media with ANCA‐Associated Vasculitis (OMAAV)?. (21st June 2017) - Hisata, Yoshio; Sasaki, Eisuke; Ishimaru, Koutaro; Harada, Yousuke; Nakano, Hirohumi; Naitou, Shinji; Sugioka, Takashi
Abstract: Hearing loss is often the only symptom of OMAAV at initial presentation, thus making early diagnosis difficult. We present OMAAV in a 70‐year‐old woman with hearing loss and dry cough. Otoscopy showed otitis media with effusion. Audiometry showed mixed hearing loss, especially in the right ear. Serum myeloperoxidase antineutrophil cytoplasmic antibody was positive. Image analyses showed lung lesion and interstitial pneumonia, while bronchoscopy showed possible microscopic polyangiitis. After starting and tapering prednisolone, respiratory and otologic symptoms improved. When examining patients with acute otologic symptoms and suspected lung and/or renal disease, OMAAV should be included in differential diagnosis.